2020
DOI: 10.1002/iub.2271
|View full text |Cite
|
Sign up to set email alerts
|

A competition between hydrophobic and electrostatic interactions in protein–ligand systems. Binding of heterogeneously halogenated benzotriazoles by the catalytic subunit of human protein kinase CK2

Abstract: A series of chlorine-substituted benzotriazole derivatives, representing all possible substitution patterns of halogen atoms attached to the benzotriazole benzene ring, were synthetized as potential inhibitors of human protein kinase CK2. Basic ADME parameters for the free solutes (hydrophobicity, electronic properties) together with their binding affinity to the catalytic subunit of protein kinase CK2 were determined with reverse-phase HPLC, spectrophotometric titration, and Thermal Shift Assay Method, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…The difference in the dissociation constant for the strongly binding site is even much smaller than DSF data suggested. We have also shown that HBBH is much less hydrophobic and less acidic than TBBt 18 , which may make it less toxic. Herein, we study the properties of two iodinated compounds: 5,6-diiodo-1 H -benzotriazole ( HIIH ) and 4,7-dibromo-5,6-diiodo-1 H -benzotriazole ( BIIB ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The difference in the dissociation constant for the strongly binding site is even much smaller than DSF data suggested. We have also shown that HBBH is much less hydrophobic and less acidic than TBBt 18 , which may make it less toxic. Herein, we study the properties of two iodinated compounds: 5,6-diiodo-1 H -benzotriazole ( HIIH ) and 4,7-dibromo-5,6-diiodo-1 H -benzotriazole ( BIIB ).…”
Section: Introductionmentioning
confidence: 75%
“… a Literature data 18 , 20 . b Two independent binding sites were identified, the second one should be assigned to the solvent exposed region located at the interface between alpha and beta subunits of CK2 32 .…”
Section: Resultsmentioning
confidence: 99%
“…RP-HPLC method, a fast and efficient alternative for standard logD determination in octan-1-ol/water system [ 42 ], was used to assess the hydrophobicity of all synthesized compounds. This method has been successfully used in our laboratory for halogenated benzotriazole derivatives, including the evaluation of the effect of hydrophobicity on their binding to the catalytic subunit of protein kinase CK2 [ 24 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is why we tested larger scaffolds with either a larger heterocyclic ring ( 6a – e , 7a – e ) or substitution in the imidazole, both of them to preserve possible interactions with a hinge. We analyzed solely dihalogenated compounds of the same pattern of halogen atoms at the benzene ring to assure that predominating interactions with the hinge region (occurring with more halogen atoms) and configuration effect (depending on the halogenation pattern) will not predominate or interfere with the interdependence we were analyzing [ 24 , 34 , 43 ]. Interestingly, for the tested halogen configuration, we can notice that only ligands with uneven charge distribution on the non-benzene ring (groups 3, 4, 5, 7) exhibit measurable affinity towards CK2, while ligands even much hydrophobic but without proton-donating groups (series 2 and 6) do not stabilize the complex (i.e., ΔT m < 1 °C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation